Shadowland - Noel, Alyson (New York St. Martin's Griffin, 2009)
Ever and Damen have traveled through countless past lives and fought off the world's darkest enemies to be together forever, but just as their long-awaited destiny is finally within reach, a powerful curse threatens them.
Sequel to: Blue moon.
960L
Keywords: Psychic ability; Immortality; Supernatural; Fantasy; Fantasy fiction; Curses; Surfers; Paranormal phinomena; Teenage boy/girls relations; High schools; High school students; Psychic ability; Young adult fiction